Factors associated with ovine footrot lesions in Uruguayan flocks: a cross-sectional study - Neto, Waldemir Santiago; Crescionini, Ana; Slimovich, Ludmila; Silveira, Caroline da Silva; Salada, Sofía; Fraga, Martín; Fierro, Sergio (Frontiers in Veterinary Science, 2025)
Ovine footrot has Dichelobacter nodosus as the primary pathogen, and it is characterized by its infectious and multifactorial nature, such as environmental conditions, management practices, and host susceptibility, leading to variable prevalence and economic impacts across regions. The present study investigated factors associated with footrot scores in individual sheep from a non-probabilistic sample of 60 flocks enrolled by the Uruguayan Wool Secretariat, from which 6,139 sheep had their feet clinically evaluated from 2021 to 2024. PCR was employed to confirm D. nodosus at the farm level, and data on flock management were collected. The occurrence of footrot-related lesions at the animal level was 17.7%, mainly due to severe footrot. Ordinal multivariable mixed models with a random farm effect showed that the intraclass correlation coefficient for farms was 57.2%. Regarding fixed effects, breed stock size, sanitary protocol at sheep admission, formalin footbath, meat production purpose, hoof trimming, and veterinarian assistance for sheep had a protective effect. In contrast, the footrot vaccine and footrot control and eradication program had a risk effect. We conclude that specific management effects influencing D. nodosus infection in Uruguayan sheep flocks could guide context-specific, preventive interventions against footrot at the farm level.